Older People and Spatial Planning and Development of a Municipality (Gmina) – Some Selected Administrative and Legal Issues - Ruczkowski, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
This study is devoted to the issues related to older people in the context of spatial planning and development of a municipality (gmina). An important component of senior citizen policy should be the appropriate solutions relating to spatial planning and development. There is no doubt that some provisions that take into account the needs of older people, especially those with reduced mobility, must be adopted in various planning documents. It is particularly important to implement such solutions that give older people access to public spaces. The adopted regulations should take into account the requirements of older adult mobility, provide access to recreational and relaxation spaces. museums, libraries and other culture institutions.